Marketing development of SMEs assisted by Lazismu Bandongan with digital marketing - R. Arri Widyanto; Alfina Khusni Rodiyatul Hidayati; Dyan Ihza Mahendra; Lina Wahyu; Nayunda Gunawan Saputri; Ika Hermeining Normawati (Community Empowerment, 2022)
Ngepanrejo Village is one of the villages in the Bandongan District which has 1,931 Micro, Small and Medium Enterprises (MSMEs) and 800 of them are registered in Ngepanrejo Village. However, MSMEs in Ngepanrejo Village which are home industries, especially traditional food such as criping lenteng and peanut crackers do not yet have branding and sales are still conventionally sold in traditional markets, so coaching is needed especially for branding and marketing. The focus of this activity is data collection on MSMEs and digital marketing to improve the marketing of their products. The activity model used in this service is Participatory Rural Appraisal (PRA) which demands an active role from the community. The result is an increase in marketing methods and added value in the field of science and technology, namely digital marketing by utilizing the Mitramu application belonging to Lazismu Bandongan.